1998
DOI: 10.1097/00005176-199809000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake and Growth of Infants with Phenylketonuria Undergoing Therapy

Abstract: Phenex-1 supports normal growth when fed in adequate amounts. These data support those of the Medical Research Council Working Party on Phenylketonuria for 3 g/kg per day of amino acids from medical food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 18 publications
1
26
1
3
Order By: Relevance
“…European studies [25-29] found similar growth retardation during the first years of life followed by restoration of the normal growth curve from the second year or later, supporting our results that 65.6% of the patients were under 10 years of age and all of them showed a significant catch up of growth at the follow-up study. In agreement with other authors, we found no correlation between phe levels and growth [24, 25, 30, 31]. However, it is clear that the outcome of growth in PKU patients depends on the therapeutic approach, genetic background and novel alimentary substitutes.…”
Section: Discussionsupporting
confidence: 92%
“…European studies [25-29] found similar growth retardation during the first years of life followed by restoration of the normal growth curve from the second year or later, supporting our results that 65.6% of the patients were under 10 years of age and all of them showed a significant catch up of growth at the follow-up study. In agreement with other authors, we found no correlation between phe levels and growth [24, 25, 30, 31]. However, it is clear that the outcome of growth in PKU patients depends on the therapeutic approach, genetic background and novel alimentary substitutes.…”
Section: Discussionsupporting
confidence: 92%
“…A smaller number of studies focused on the relation of head circumference and protein intake in PKU infants, but the results of these studies were not conclusive (Acosta and Yannicelli 1994;Acosta et al 1998). Studies that investigated causes for the retarded height growth in PKU patients focused on low blood Phe concentrations, a deficiency of tyrosine or a deficient intake of total protein.…”
Section: Lc-pufa In Infancy and Childhoodmentioning
confidence: 99%
“…It may influence growth, as there are differences in growth patterns between various groups/countries (Verkerk et al 1994; Hoeksma et al 2005; Acosta et al 1998; Schaefer et al 1994; Dobbelaere et al 2003). It clearly may result in deficiencies of, for example, long-chain unsaturated fatty acids and vitamin B 12 (Hanley et al 1993; Hvas et al 2006; Huemer et al 2008).…”
Section: Drawbacks Of the Dietary Treatmentmentioning
confidence: 99%